Effects of Applying Hydrotherapy on Quality of Life in Women with Multiple Sclerosis - Somayyeh Ghaffari; Fazlollah Ahmadi; Seyyed Masoud Nabavi; Anoushirvan Kazem-Nezhad (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Multiple Sclerosis (MS) is one of the most common chronic diseases of the central nervous system (CNS), which causes important changes patient's life, specially in adults life. MS decreases the quality of life (QOL) of patients severely and led to disability gradually. The aim of this study is to assess the effects of applying hydrotherapy on quality of life of Multiple Sclerosis patients. Materials & Methods: In this Quasi-experimental study, 50 Multiple Sclerosis patients were selected with no probability sampling according to specific criteria and then assigned to experimental and control groups (25 patients in each group) with balanced randomized allocation. Hydrotherapy performed for 24 sessions by experimental group during three months but no intervention was done for control group. Data collector tools included: demographic questionnaire, SF8- QOL questionnaire, Self report checklists. Statistical analysis was done by use of statistical tests such as: chi square, paired t-test, student t-test, ANOVA with repeated measurements and independent t-test.  Results: There was no significant difference between two groups in phycical and mental dimensions (P=0.04 & P=0.2) and whole (P=0.81) scores of QOL before intervention, but there were significant differences between two groups after intervention in these scores (P<0.001, P=0.003 & P<0.001). ANOVA test with repeated measurements showed that there is significant difference in mean score of whole (P=0.04) and physical (P=0.05) and mental (P=0.04) dimensions of QOL between two groups in 4 times. Conclusion: Hydrotherapy is practically feasible and is associated with increase of MS patient ,s QOL so that applying this technique can promote MS patient ,s QOL and offered to these patients.